Peru : Selected Issues Paper. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper assesses empirically the motives and effectiveness of foreign exchange (FX) interventions in Peru. The results of the study indicate asymmetries both in the Central Reserve Bank of Peru's reaction function and in the effectiveness of FX interventions. Probit estimates of the likelihood of FX purchases and sales, in the first stage of the regression, show that both forms of intervention are targeted at leaning against the wind; that is, resisting appreciation in the former case and resisting depreciation in the latter. But only FX sales, not FX purchases, react to volatility. Similarly, instrumental variable regression results show evidence of asymmetry in the effectiveness of FX interventions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet